Magia czasu wojny. Współczesne praktyki magiczne w perspektywie wojen XX wieku i konfliktu w Ukrainie (Przegląd Religioznawczy – The Religious Studies Review, 2023)
This article explores the issue of magical thinking and occult practices in the context of war. Especially in the wars of the 20th century and the current war in Ukraine, there are many examples of how magic is being used and referred to in war propaganda. The Russian accusations of Satanism and occult involvement in the 2022 phase of the war are striking examples of such phenomena. The article presents a theoretical approach to magic in social sciences, with a focus on social anthropology. However, a historical context is also revealed in which modern magical practices during times of war gain more significance and are placed within a broader social and political framework. This allows for drawing conclusions in the comparison between Russia’s current obsession with the occult and Nazi occultism in the first half of the 20th century.